THE ROLE THEOF FINANCIAL SERVICES AUTHORITY OF INDONESIA IN ORDER TO SUPPORT RURAL BANK/ISLAMIC RURAL BANK SUSTAINABILITY - Maria Widyastuti; Stephanie Astrid Ayu (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The financial services authority (OJK) released data, in all of Indonesia half of the existing rural bank/Islamic rural banks have not met the minimum capital according to the Financial Services Authority Regulation (POJK) No.5/POJK.03 / 2015, which is IDR 3 billion and IDR 6 billion according to the size of their business so far, until December 31, 2019. Of course, with the data released by the OJK, many rural bank/Islamic rural banks will be forced to stop their operations. This research aims to analyze the role of POJK in supporting the sustainability of rural bank/Islamic rural banks. This research was carried out through the following stages: 1) the researcher conducted in-depth interviews with informants with a questionnaire guide; 2) to support the results of the interview, a literature study was also conducted, especially regarding regulations related to marketing products / services; 3) from the results of the interview tabulations are made to make it easier to read the results of the interviews, 4) discuss the tabulated data so that the condition of the rural bank/Islamic rural banks can be seen, 5) make conclusions. The results of this research found that rural bank/Islamic rural banks with a fund of Rp.500,000,000, - for the time being unable to cover the risk that must be borne by rural bank/Islamic rural banks, it is necessary to have a POJK which regulates the minimum core capital. POJK is also very much needed so that rural bank/Islamic rural banks can run their business more efficiently, effectively, transparently and accountably and be able to compete fairly with other financial institutions. Keywords : POJK, rural bank/Islamic rural banks sustainability